IMPLIKASI HUBUNGAN PERDATA ANAK LUAR PERKAWINAN DENGAN LAKI-LAKI SEBAGAI AYAHNYA - Masykuroh, Yufi Wiyos Rini (Universitas Islam Negeri Raden Intan Lampung, 2016)
Based on the Constitutional Court Number 46 /PUU-VII / 2010, the civil relationship between childwith his father and his father's family based on theirblood relationship between the child and his fatherand mother, although the both do not have themarriage bound. The imperfections of maritalrelationship between the father and mother did notabolish their blood relationship and civil relationshipbetween a child and his biological father as a civilrelationship between a child and his biologicalmother. To find the right meaning of the phrase“civil relations children nonwedlock with a man ashis father” in the Constitutional Court decision No.46 / PUU-VIII / 2010, is to observe opinions fromlegal experts. Therefore, this discussion is intendedto find answers to the meaning and scope of civilrelations between children nonwedlock with a manas his father, by analyzing the opinion of a numberof academics and legal practitioners who havecompetence in this field.